مروجہ حیلۂ تملیک کا شرعی جائزہ: A Shariah Review of the Prevailing Heela of Tamlik - Israr ullah Mashwani; Prof. Dr. Mohyuddin Hashmi (Al Manhal Research Journal, 2024)
Most of the sources of income of religious schools in addition to donations consist of Zakat, Ushar, Nazar etc. The costs of religious schools are also different. For example, staff salaries, accommodation expenses, student scholarships and payment of various utility bills etc. Because not every type of wealth can be spent on every type of consumption, rather, they can spend the amount of Zakat, Ushar and Nazar on certain expenses, while on some other expenses only sadakat can be spent and not Zakat etc. Sometimes the needs of a madrassa become too much, and it is not possible to manage from charity fund to meet them. In such a situation, these needs are fulfilled by making “Heela Tamlik ” in Zakat wealth. Now the question arises that how to use the wealth of zakat to spend on non-consumables by “Heela Tamlik”? The article under review is the answer to this question. In this article, the Shari'ah review of the prevailing “Heela Tamlik” has been done.